'It Ain't Necessarily so': Eliciting Hidden Knowledge and the Role of Schemata in Data Collection1. (December 2016) - Roberts, David
A problem for evaluators and researchers is that what people 'say' in an interview context is often different from what they do in the everyday world, in vivo. Elicitation techniques appear to be effective at revealing 'hidden' data but the theories about why they do so are inadequate. This paper examines literature from cognitive science, schema and survey research to identify ideas that may help explain why elicitation techniques work and how we can improve their use. The schema concept provides a testable mechanism for how elicitation may function and the conditions under which elicitation might work. It also raises questions for evaluators about the variability of people's responses in different contexts and the influence of the interview context on the results obtained.